Application-Specific Integrated Circuits - Smith, Michael John Sebastian (New Delhi Pearson Education, 1997)
Dealing with application-specific integrated circuits (ASICs), this book describes the methods in VLSI-systems design. It covers both semicustom and programmable ASIC types. It also describes ASIC logic design - design entry, logic synthesis, simulation, and test - and then to physical design - partitioning, floorplanning, placement, and routing.
Keywords: Electronic circuits 621.3815